Size, Value, and Momentum Effects in Portfolio Returns: Evidence from India - H. R., Tejesh; M., Khajabee (Indian Journal of Research in Capital Markets, 2024)
Purpose : The study attempted to evaluate the applicability of the capital asset pricing model (CAPM), the Famaâ€“French three-factor model (FF3FM), and the Carhart four-factor model (C4FM) in the Indian stock market. The increasing complexity of financial markets and the need for more accurate models to capture risk-return relationships motivated this comparative analysis over 12 years. Methodology : The study was based on secondary data covering 12 years, from March 2012 to March 2024. This investigation used monthly time series data. Market capitalization (size), book-to-market equity ratio (value), and monthly average returns (momentum) are used to build 15 univariate sorting portfolios. These portfolios served as the dependent variables. Additionally, three independent risk factors, i.e., small minus big (SMB), high minus low (HML), and winners minus losers (WML) were constructed using a 2 Ã— 3 sorting strategy along with excess market return (EMR). The analysis was conducted using these portfolios to evaluate the asset pricing models with RStudio version 2024.04.2 + 764. Findings : In terms of explaining variances in portfolio returns, the study concluded that the 3FM performed better than the CAPM. Additionally, compared to the 3FM, the 4FM offered a more thorough explanation that captured the risk-return relationship in the Indian stock market, demonstrating its efficacy in assessing investment success. Practical Implications : It was recommended that investors and financial analysts consider the C4FM for a more accurate assessment of stock returns in the Indian market. The study acknowledged its limits and recommended that further research look into other recently developed characteristics that may have an impact on the risk-return connection in various market scenarios, such as profitability and investment. Originality : Unlike previous research that mainly focused on developed markets, the study provided a comparative analysis of the CAPM, FF3FM, and C4FM in the context of the Indian stock market. It offered new insights into their applicability and performance in emerging markets.